Holy Rover : Journeys in Search of Mystery, Miracles, and God - Erickson, Lori (Book collections on Project MUSE., 2017)
From her childhood on an Iowa farm, Lori Erickson grew up to travel the world as a writer specializing in holy sites--journeys that led her on an ever-deepening spiritual quest. In Holy Rover, she weaves her personal narrative with descriptions of a dozen pilgrimages. Her trips give Erickson the chance to reflect on her Lutheran upbringing, her flirtation with Wicca, and her admiration for Tibetan Buddhism. A trip to the healing shrine of Lourdes is intertwined with the story of her son's serious illness as a baby, while visiting Thoreau's Walden Pond blends with ruminations on being a writer. Along the way, Erickson encounters spiritual leaders who include the chief priest of the Icelandic pagan religion of Asatru, a Trappist monk at Thomas Merton's Gethsemani Abbey, and a Lakota retreat director at South Dakota's Bear Butte. Both irreverent and devout, Holy Rover includes images of holy sites around the world taken by several of the nation's leading travel photographers. Travel writer, Episcopal deacon, and author of the Holy Rover blog at Patheos, Erickson is an engaging guide for pilgrims eager to take a spiritual journey. Her book describes travels that changed her life and can change yours, too.